N1-dansyl-spermine: a potent polyamine antagonist. - RYDER, SHEILA (My University, 2004)
The potential polyamine antagonist action of N1-dansyl-spermine (a potent NMDA antagonist) was assessed in two in vivo mouse models of polyamine action. Co-administration of N1-dansyl-spermine (2?10 ?g, i.c.v.) with spermine (100 ?g, i.c.v.) resulted in a dose-dependent antagonism of the spermine-induced CNS excitation (body tremor and fatal tonic convulsions). In addition, the same dose of N1-dansyl-spermine antagonised spermine's enhancement of NMDA-induced convulsions. These results suggest that N1-dansyl-spermine is in vivo a potent antagonist of the CNS effects of spermine and of its action at the positive polyamine modulatory site on the NMDA receptor.
PUBLISHED
PMID: 15140645
Keywords: Spermine; N-methyl-D-aspartate; N1-dansylspermine; Convulsion; Spermine; Polyamine; Excitotoxicity; Spermine; Methyl aspartate; Convulsions